Metabolic Alterations in Human Post‐Mortem Frontal Cortex and Cerebrospinal Fluid Associated With High Levels of Nicotine Metabolite Cotinine - Masvosva, Wadzanai; Lehtonen, Marko; Martiskainen, Mika; Tiihonen, Jari; Karhunen, Pekka J.; Hanhineva, Kati; Rysä, Jaana; Kok, Eloise; Kärkkäinen, Olli (Wiley-Blackwell, 2025)
Cigarette smoking is the single most significant cause of preventable death in the world. Tobacco smoking causes exposure to thousands of chemicals and disrupts biological pathways. It impacts several organs, including the brain, where its effects are mediated by nicotinic acetylcholine receptors. Women seem to be more susceptible to the negative health effects of smoking. In this study, we focused on the changes in the metabolic profile of human postmortem frontal cortex and cerebrospinal fluid (CSF) samples associated with high levels of the nicotine metabolite cotinine. We used non-targeted metabolomics to analyse post-mortem frontal cortex and CSF samples from the Tampere Sudden Death Study cohort. We identified 137 cases (24 females) with high cotinine levels, indicating nicotine exposure. For controls, we identified 82 subjects (20 females) with no cotinine in the frontal cortex or CSF samples and no known history of smoking based on medical records and autopsy reports. Cases had significantly higher levels of 1-methylhistamine (Cohen's d = 0.66, p < 0.0001) and N-acetylputrescine (d = 0.84, p < 0.0001), and lower levels of aspartic acid (d = −0.53, p < 0.001), 3-methylhistidine (d = −0.58, p = 0.0004) and taurine (d = −0.47, p = 0.0002) in the frontal cortex compared to controls. Compared to the frontal cortex, differences between cases and controls were smaller in the CSF samples. Most of the observed differences were similar in both sexes, with a few exceptions like low ergothioneine levels, observed especially in female cases. In conclusion, smoking or nicotine exposure is associated with alterations in metabolites linked to increased oxidative stress and neuroinflammation, as well as reduced neurotransmitter levels in the frontal cortex.